Treponema denticola interactions with host proteins - Fenno, J. Christopher (Co-Action Publishing, 2012)
Oral Treponema species, most notably T. denticola, are implicated in the destructive effects of human periodontal disease. Progress in the molecular analysis of interactions between T. denticola and host proteins is reviewed here, with particular emphasis on the characterization of surface-expressed and secreted proteins of T. denticola involved in interactions with host cells, extracellular matrix components, and components of the innate immune system.